Collusive Tendering Damages Construction Services Business Competition - Ferdinald, Donald Junius; Manurung, Edison Hatoguan; Wasito, Kasimir (International Journal of Sustainability in Research, 2023)
Collusion in the construction services industry has proven to be detrimental to business competition. Collusive practices in the tender process hinder fair competition and result in significant economic losses. Companies involved in such collusion cooperate to manipulate bidding prices, avoid genuine competition, and influence tender outcomes to their advantage. As a consequence, companies not engaged in the collusion lose opportunities to secure contracts, while project costs escalate. Collusive tendering also has negative impacts on the quality of construction work. When companies collude to win tenders, they may disregard necessary quality and safety standards. This can lead to lower quality, unsafe projects, and increased infrastructure failure risks. Furthermore, collusive tendering creates an unfair environment for small and new companies attempting to enter the construction market. They often struggle to compete with large companies involved in the collusion, which have advantages in resources and experience. As a result, innovation and healthy competition in the construction services industry are hindered, and the market becomes dominated by a few major players. To combat collusive tendering, crucial steps need to be taken. Governments and procurement agencies should enforce strict and effective regulations to prevent and penalize dishonest practices. Transparency in the tendering process, rigorous scrutiny of collusive practices, and severe sanctions for violations must be implemented. Additionally, awareness and active participation from all stakeholders, including construction companies, governments, and the public, are essential in addressing collusive tendering. By eliminating collusive tendering, the construction services industry can foster fair competition, encourage innovation, improve the quality of work, and provide equal opportunities for all participating companies in the market.